Peningkatan Kemampuan Problem Solving Matematis Pada Siswa Kelas 3 Melalui Media Interaktif - Arahra, Ayatusifa; Rakhmat, Cece; Zahrah, Riza Fatimah (Journal Of Dehasen Educational Review, 2024)
Learning that occurs in class III B SDN 1 Rahayu where students' assessment of math learning is still relatively low. Judging from the average value of math test scores on multiplication material from 21 only 9 people or 30% of students are above the KKM (Minimum Completeness Criteria) and only 12 people or 70% of students are below the KKM (Minimum Completeness Criteria) with an average value of 55/60, while the KKM value is 75. Therefore, it is necessary to conduct classroom action research (PTK) using two cycles to find out significant progress. From the results of the research for two cycles in cycle I only reached (89.06%) then because the active learning process was fun and not monotonous so that there was an increase in learning in Cycle II which reached (96.87%), there was an increase of 7.81%. In the implementation of improvements, in cycle I teacher activity in managing learning reached (79.46%) although there were several obstacles in cycle I and improvements in cycle II with a percentage of (84.37%) but there was an increase (4.91). ABSTRAK Pembelajaran yang terjadi di kelas III B SDN 1 Rahayu dimana penilaian siswa terhadap pembelajaran matematika masih tergolong rendah. Dilihat dari nilai rata-rata nilai ulangan matematika pada materi perkalian dari 21 hanya 9 orang atau 30% siswa yang berada di atas KKM(Kriteris Ketuntasan Minimal) dan hanya 12 orang atau 70% siswa berada di bawah KKM (Kriteris Ketuntasan Minimal) dengan rata-rata nilai 55/60, sedangkan nilai KKM yaitu 75. Oleh sebab itu perlu adanya penelitian tindak kelas (PTK) dengan menggunakan dua siklus untuk mengetahui kemajuan yang signifikan. Dari hasil penelitian selama dua siklus pada siklus I hanya mencapai (89,06%) kemudian karena proses pembelajaran yang aktif menyenangkan dan tidak monoton sehingga adanya peningkatan pembelajaran di Siklus II yang mencapai (96,87%) maka terjadi peningkatan sebesar 7,81%. Dalam pelaksanaan peningkatan, pada siklus I aktivitas guru dalam mengelola pembelajaran mencapai (79,46%) meskipun ada beberapa kendala dalam siklus I dan perbaikan di siklus II dengan presentase (84,37%) tetapi terjadi adanya peningkatan (4,91).